RELATIVE EFFICACY OF VARIOUS TREATMENT PROCEDURES EMPLOYED TO RELIEVE DYSTOCIA IN CANINES - MURTHY, NARASIMHA; DEVARAJ, M; KRISHNASWAMY, A; HONNAPPA, T G (The Indian Journal of Animal Reproduction, 2023)
Studies were conducted to analyze the efficacy of different treatment procedures employed to relievedystocia in bitches (n=240). In the present study medical treatment using oxytocin, calcium and dextrose eitheralone or in combination was employed to treat only cases of primary complete or primary partial uterine inertiaand the treatment protocol was successful in only 16.67 per cent of the cases. Nearly 83 per cent of cases ofprimary uterine inertia failed to respond to medical treatment and had to be subjected for cesarean section. Thevaginal manipulative procedures to relieve dystocia using gloved finger or sponged forceps was successful inrelieving 15.41 per cent of cases of obstructive dystocia and the rest had to be subjected for cesarean section.Cesarean section had to be carried out in 67.91 per cent of all cases of dystocia encountered in the presentstudy. The higher frequency of cesarean section employed to relieve dystocia in small animals may possiblydue to small size of the animal, multiparous nature, long duration of delivery and demands by the owner todeliver as many live puppies as possible.
Keywords: Canine; Dystocia; Caesarean section